Обґрунтування процесу ефективного живлення і конструкційної схеми дозуючо-живильного пристрою зерноочисного модуля універсальних пневмовібровідцентрових сепараторів зерна - Прилуцький, А. Н.; Prylutsky, А. (КНТУ, 2014)
Викладено результати досліджень процесів дозування і живлення пневмовідцентрових і вібровідцентрових решітних робочих органів сепараторів зерна з вертикальним розміщенням осей обертання, сформульовано технологічні вимоги до дозуючо-живильних пристроїв, обґрунтовано процес ефективного живлення, конструкційна схема і основні параметри дозуючо-живильного пристрою зерноочисного модуля універсальних пневмовібровідцентрових сепараторів зерна. The purpose of research. Justification process efficient supply and structural schemes Dosing-feeding device universal module grain separators vertical axis placement of separating, in the shape of the surface of rotation or circular air channels will increase the effectiveness of separation and avoid injury grain. There are results of researching dosing processes and supply pneumocentrifugal and vibrocentrifugal sieve grain separators working bodies with a vertical axis of rotation. The technological requirements for metering and supply units are formed, are justified process of effective supply, constructive scheme and main parameters metering and feeding device module of universal pneumovibrocentrifugal grain separators . Developed methodology for calculations to determine the technological and structural parameters of the supaply - dispensing device. Conclusions:1. Formulated technological requirements Dosing-feeding device universal module winnowing grain separators. 2. based process and supply efficient structural scheme Dosing-feeding device. 3. The developed technique of calculation to determine the technological and structural parameters Dosing-feeding device.
Underlying the process of effective power and constructive scheme metering and feeding device module universal pneumovibrocentrifugal winnowing grain separators
Keywords: сепарація; дозування; розподілення; рівномірність; ефективність; separation; dosing; distribution; uniformity; efficiency